2013
DOI: 10.1177/1470320313492361
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin-converting enzyme I/D polymorphism and sepsis: A meta-analysis

Abstract: Our meta-analysis confirmed that the angiotensin-converting enzyme I/D polymorphism was associated with sepsis risk. However, the angiotensin-converting enzyme I/D polymorphism was not associated with sepsis mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These findings matched with our results that there is no relationship between ACE polymorphism and sepsis. Also, Hou et al 23 elucidated no association between the I/D genotype and infant mortality, which enhances our results. However, during sepsis, ACE activity is decreased with the blood pressure.…”
Section: Ras Activation May Influence Lung Injury By Modifying Vascul...supporting
confidence: 78%
See 1 more Smart Citation
“…These findings matched with our results that there is no relationship between ACE polymorphism and sepsis. Also, Hou et al 23 elucidated no association between the I/D genotype and infant mortality, which enhances our results. However, during sepsis, ACE activity is decreased with the blood pressure.…”
Section: Ras Activation May Influence Lung Injury By Modifying Vascul...supporting
confidence: 78%
“…19 Our findings are in line with those of Sivasli et al 14 , who reported that D/D and D-alleles were significantly higher in premature neonates without RDS than in neonates with RDS (43.5% and 68.5% vs. 26.8% and 47.6%, p<0.05), which suggested that D/D and D-alleles are protective factors from RDS in premature neonates. In contrast, Yimenicioglu et al 1 23 observed that D/D was a protective factor for sepsis in both the adult and pediatric populations in their meta-analysis study, and ACE inhibitor drugs may be harmful to patients with sepsis. These findings matched with our results that there is no relationship between ACE polymorphism and sepsis.…”
Section: Ras Activation May Influence Lung Injury By Modifying Vascul...mentioning
confidence: 89%
“…Genotyping control quality was assessed by (i) analysing the correlation between the original and the duplicate genotype in 10% of the samples randomly chosen; and (ii) assessing the Hardy–Weinberg equilibrium .…”
Section: Methodsmentioning
confidence: 99%
“…In ventilated low birth weight infants the ACE insertion/deletion (I/D) polymorphism does not have a significant effect on the incidence or outcome of sepsis [210,211]. Studies and meta-analyses showed that carriers of I allele (D/I genotype and I/I genotype) were at increased sepsis risk [212][213][214], but the polymorphism is not associated with outcome in critically ill septic patients [214,215]. With regard to ARDS, the data of Villar et al [216] do not support an association of the ACE gene I/D polymorphism with susceptibility or mortality in severe sepsis or with sepsisinduced ARDS in Spanish patients, but Cardinal-Fernandez et al demonstrated that the presence of the allele D of the ACE gene is associated with ARDS in patients with severe sepsis [217].…”
Section: Angiotensin-converting Enzyme (Ace)mentioning
confidence: 99%
“…-Insertion/deletion (I/D) polymorphism does not have an effect on the incidence or outcome of sepsis in ventilated low birth infants [210,211] -Carriers of the I allele at increased sepsis risk [212][213][214] -I polymorphism not associated with outcome in critically ill septic patients [214][215][216] -The presence of the D allele is associated with ARDS in patients with severe sepsis [217] Sepsis…”
Section: Diagnostic Significance Prognostic Significancementioning
confidence: 99%